Improving P-Doped DBRs Operation at Cryogenic Temperatures: Investigating Different Mirror Geometry - Behzad Namvar; Topi Uusitalo; Heikki Virtanen; Mircea Guina; Jukka Viheriala (IEEE Photonics Journal)
The use of vertical-cavity-surface-emitting lasers with ability to operate at cryogenic temperatures (Cryo-VCSELs) is a promising path to implement optical data links between superconducting processors maintained in cryogenic environments (4 K range) and room temperature (RT) computing hardware. In order to achieve energy-efficient operation of a cryo-VCSEL, whether by passing current through the mirrors or utilizing intra-cavity contacts, a critical bottleneck for improving the operation is related to the p-doped distribute Bragg Reflectors (DBRs). This is because holes exhibit lower mobility and lower thermal conductivity compared to their n-side counterparts. To determine the actual temperature of an operating p-doped DBR and its impact on the behavior of the DBRs and the cryo-VCSEL, a thermal simulation using the finite-element method was conducted and validated with experimental results. Furthermore, we explored different mirror geometries to optimize both current flow and the growth complexity of the DBR. DBR layers with various interface shapes, such as uni-parabolic grading and three to five steps with different Al mole fractions, have been investigated. As a result of the study, we achieved more efficient operation at cryogenic temperatures, with a 60% reduction of the series resistance and a 39% reduction of the voltage penalty related to the p-doped DBR.